The Role of Transformational Leadership in Encouraging Innovation in Indonesian Startup Companies - Rahman , Maha Abdul-; Al-Rubaie, Hasan; Al-Khalil, Samira (Journal of Loomingulisus ja Innovatsioon, 2024)
In recent years, Indonesia’s startup ecosystem has experienced rapid growth, driven by technological advancements and increased entrepreneurial activity. However, despite the growing number of startups, many face challenges in fostering innovation, which is crucial for their success and sustainability. One of the key factors influencing innovation in organizations is leadership. Transformational leadership, which inspires and motivates employees to exceed their expectations and embrace change, has been identified as a potential driver of innovation. This research aims to examine the role of transformational leadership in encouraging innovation within Indonesian startup companies. The study explores how transformational leadership behaviors influence employees’ creativity, motivation, and overall organizational innovation. A mixed-methods approach was employed, combining qualitative interviews with startup founders and employees, and quantitative surveys measuring leadership styles and innovation outcomes. Data was collected from 15 Indonesian startups across various industries, and analyzed using thematic analysis and regression techniques. The findings reveal that transformational leadership significantly contributes to fostering a culture of innovation within startups. Leaders who demonstrate vision, intellectual stimulation, and individualized consideration were found to enhance employee creativity and innovation. The study concludes that transformational leadership is crucial for promoting innovation in Indonesian startups. It highlights the need for leaders to cultivate a supportive, inspiring environment to drive continuous innovation.